"Água para todo e sempre": políticas públicas de saneamento em Ituiutaba-MG (1970-1980) - Silva, Maria Angélica da Costa (2018)
This work aims to discuss the effect of federal public policies on health and sanitation in the Ituiutaba-MG region, between 1970 and 1980. This period corresponds to the moment of consolidation of the municipal authority SAE - Ituiutaba Water and Sewage Superintendence. During the process of urban modernization of the city, the water supply system became one of the primordial elements of this process. The SAAEs are simple water supply systems installed in several municipalities through SESP - Special Public Health Service. It has been transformed into SESP Foundation in the 1960s. Initially, the agency was created through a bi-lateral agreement between the United States and Brazil for the war effort in 1942. After that, SESP became the initial step towards the implementation of sanitary policies at the federal level, serving the states and municipalities in urban and rural areas, with sanitation, combating endemics, health education, training of agents and prophylaxis.